2019
DOI: 10.1200/jco.2019.37.15_suppl.e23064
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes for dental health, shoulder-neck dysfunction, and overall quality of life after treatment with radiation for head and neck cancer.

Abstract: e23064 Background: The current exploratory cross-sectional study was designed to better characterize survivorship issues among patients treated with radiation for head and neck cancer with regard to dental health, shoulder-neck dysfunction, and overall quality of life. Methods: Patients (n = 58) being seen for follow-up at a radiation oncology clinic at least one year beyond the end of treatment completed three survey questionnaires: the EORTC Core Quality of Life Questionnaire (EORTC QLQ-C30), the EORTC Head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The post‐treatment period is normally characterized by gradual recovery and improvement; however, only global health status/QoL seems to reach pretreatment levels within 1 year after treatment completion . Thus, the following year(s) of HNC survivorship is characterized by persistent treatment‐related side effects accompanied by deteriorated functional status …”
Section: Introductionmentioning
confidence: 99%
“…The post‐treatment period is normally characterized by gradual recovery and improvement; however, only global health status/QoL seems to reach pretreatment levels within 1 year after treatment completion . Thus, the following year(s) of HNC survivorship is characterized by persistent treatment‐related side effects accompanied by deteriorated functional status …”
Section: Introductionmentioning
confidence: 99%
“…For instance, Verma et al previously found that in a population of patients treated for head and neck SCC, nearly 40% experienced nocturnal neck or shoulder pain but only 31% reported being counselled regarding potential shoulder problems prior to treatment. 17 Additionally, our study observation that patients primarily experienced decline in social and functional activities such as recreation, lifting objects, and performing daily work is especially notable given that persistent reductions in physical activity have been correlated with fatigue and reduced social and emotional well-being in head and neck cancer survivors. 26 Thus, understanding the severity of HPV + OPSCC treatment-induced neck and shoulder pain and identifying patients suitable for referral to physical therapy-based interventions can also help to improve survivorship care.…”
Section: Discussionmentioning
confidence: 82%
“…15,16 Regardless of aetiology, shoulder pain and dysfunction after oncologic treatment may greatly affect QOL and functional status, including ability to perform daily activity, sleep comfortably, and lift objects. 17 This QOL impact has been well-studied after ND with estimates that even 25%-50% of patients will demonstrate some degree of shoulder deficits postoperatively, even with selective NDs. [18][19][20] The effects of XRT and CXRT have been less well established with conflicting data regarding degree of impact on shoulder function.…”
Section: Discussionmentioning
confidence: 99%